'A sorrow shared …': a qualitative content analysis of what couples with recurrent miscarriages expect from one another and their families and friends. Issue 3 (21st July 2022) - Jansen, C; Kuhlmann, E; Scharli, P; Schick, M; Ditzen, B; Langer, L; Strowitzki, T; Kuon, R -J; Wischmann, T
Abstract: STUDY QUESTION: When couples have to face recurrent pregnancy loss (RPL), what are the partners' wishes and needs and what is their perception of helpful and unhelpful factors with regard to their own, their partners' and their families' and friends' ways of dealing with the problem? SUMMARY ANSWER: Women and men with repeated miscarriages want open communication about their losses, but expect a sensitive and empathetic attitude from others, not pity or trivialization. WHAT IS KNOWN ALREADY: RPL not only causes the women affected and their partners considerable emotional distress; it also has an impact on the couples' relationships and the way they relate to their families and friends. Studies suggest that women have a greater need than their male partners to talk about their losses and that these differences may lead to dissatisfaction and cause relational tension. In addition, men often assume a 'mainstay' role, supporting their partners and displaying fortitude in the face of distress. As yet, however, little research has been conducted so far on the question of what the members of couples with RPL expect from one another and from their families and friends. STUDY DESIGN, SIZE, DURATION: The study sample consisted of 147 couples and 17 women with at least 2 miscarriages attending the special unit for RPL at the University Women's Hospital in Heidelberg (Germany) for the first time between September 2018 and October 2020 (response rate: 82.7%). The patients were asked to participate in this combined qualitative and questionnaire study. PARTICIPANTS/MATERIALS, SETTING, METHODS: In order to explore the wishes and needs of those affected in more detail, the free text responses obtained were examined in this study by using qualitative content analysis. Categories and subcategories were created inductively to summarize and systematize content. MAIN RESULTS AND THE ROLE OF CHANCE: Patients affected by RPL want their partners and their families and friends to deal with the topic openly and empathically. In the partnership itself, acceptance of individual grieving modes and sharing a common goal are important factors. Men, in particular, want their partners to be optimistic in facing up to the situation. Regarding communication with family and friends, it transpired that 'good advice', playing the matter down, inquiries about family planning, pity and special treatment are explicitly not appreciated. LIMITATIONS, REASONS FOR CAUTION: The sample was a convenience sample, so self-selection effects cannot be excluded. In addition, the level of education in the sample was above average. Accordingly, the sample cannot be regarded as representative. The results of the content analysis are based on the respondents' written answers to open-ended questions in the questionnaire. Unlike qualitative interview studies, further questioning was not possible in the case of ambiguities or to request more details. WIDER IMPLICATIONS OF THE FINDINGS: Frank and sincere communication about miscarriages and about one's own emotions and needs should be promoted both in the partnership and among family members and friends in order to strengthen the potential of social support as a resource. Open communication about the different needs of both partners is necessary to create mutual understanding. The results show the importance not only of empathy and consideration for the couples concerned but also their desire not to be pitied. Striking a fine balance between fellow-feeling and pity may also lead to tension, and this potential dilemma should be addressed in psychosocial counselling. Overall, the study contributes to a better understanding of what couples want from their families and friends when they are attempting to come to terms with RPL and highlights potential challenges in the interaction between affected couples and their families and friends. STUDY FUNDING/COMPETING INTEREST(S): No funding was received for this study. None of the authors declared any conflicts of interest. TRIAL REGISTRATION NUMBER: DRKS00014965.